Efeitos da suplementação com óleo de coco em pacientes com hipertensão arterial de estágio 1 - Oliveira Júnior, Francisco Antônio de (2019)
The impact generated by hypertension on health continues to rise despite the advance in antihypertensive pharmacology and the knowledge about the mechanisms underlying the systemic arterial hypertension. Alternatively, to traditional pharmacological treatment, we hypothesized that dietary supplementation with extra virgin coconut oil (OCEV), alone or in combination with aerobic exercise training, could exert antihypertensive effects in patients with stage 1 hypertension. For this, 46 (forty-six) hypertensive volunteers of both genders, aged 42.5 ± 11.7 years were divided between two groups (trained and non-trained) and submitted to a placebo-controlled clinical trial to evaluate the effects of extra virgin coconut oil supplementation (10ml / day) for an experimental period of 30 days. This study was approved by the Research Ethics Committee of the Lauro Wanderlei University Hospital obtaining certification number 1.523.128/ 2016. After screening and recruitment, patients were examined by 24-hour ambulatory blood pressure monitoring, analysis of heart rate variability, blood collection for analysis of serum total cholesterol, HDL, LDL, triglycerides and glucose, malondialdehyde and antioxidant capacity total. Additionally, nutritional analysis, anthropometric assessment and body composition were performed. Data were expressed as mean and 95% confidence interval and treated with Student's t-test or mixed between-within subjects’ analysis of variance, followed by Bonferroni post-hoc test and p <0.05. Results indicate that OCEV consumption had no adverse effects on patients during the supplementation period. Although OCEV promotes an increase in caloric intake compared with placebo supplementation (1861 kcal [95% CI = 1656 - 2066] vs 1613 kcal [95% CI = 1400 - 1826]; p = 0.03), patients did not have significant changes in anthropometric variables. No significant differences were observed between experimental groups in serum total cholesterol concentrations (F (1.41) = 0.924; p = 0.333 and η2 = 0.022); LDL (F (1.41) = 3.790; p = 0.058 and η2 = 0.085) HDL (F (1.41) = 1.562, p = 0.219 and η2 = 0.038); triglycerides (F (1.41) = 0.584; p = 0.440 and η2 = 0.014) and there was no interaction of effects. There was no OCEV effect on blood glucose (F (1.41) = 0.069; p = 0.795 and η2 = 0.002), although blood glucose values showed a different pattern of change between patients supplemented with OCV and placebo over the experimental period (F (1.41) = 5.020; p = 0.031 and η2 = 0.117). There was no effect on serum MDA concentrations (F (1.41) = 0.391; p = 0.535 and η2 = 0.010) associated with OCEV alone or combined with aerobic training, but, similarly to what occurred for glycemia, there was an effect of the interaction of the type of supplementation used during the experimental period ( F (1.41) = 8.147, p = 0.007 and η2 = 0.169). This response was not reflected in the total antioxidant capacity (F (1.35) = 0.544; p = 0.466 and η2 = 0.015). No significant changes were identified on systolic (F (1.38) = 3.217; p = 0.081 and η 2 = 0.078), diastolic (F (1.38) = 0.350; p = 0.558 and η2 = 0.009) and mean blood pressure levels (F (1.38) = 1.498; p = 0.228 and η2 = 0.038) in any group after the trial period. Finally, blood pressure variability data did not show an isolated effect of treatment, but ratify the effect of interaction between type of supplementation over time: F (1.39) = 5.564, p = 0.023, η2 = 0.125, λ = 0.875) in relation to MAP. However, this response was not confirmed by the heart rate variability parameters: SDNN (F (1.17) = 0.274; p = 0.608 and η2 = 0.017), RMSSD (F (1.17) = 0.946; p = 0.345 and η2 = 0.056), SDNN / RMSSD ratio (F (1.17) = 1.449; p = 0.246 and η2 = 0.008) and SD2 / SD1 (F (1.17) = 2.063; p = 0.170 and η2 = 0.114). In conclusion, OCEV supplementation (10ml / day) for a period of 30 days, alone or in combination with aerobic exercise training, was not able to induce therapeutic effects on stage 1 hypertension in humans. In addition, it did not promote significant changes in anthropometric and lipid profile parameters. Finally, it showed no direct association with the improvement of oxidative stress and autonomic function of hypertensive patients.